2019
DOI: 10.3167/gps.2019.370201
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalism and Welfare Chauvinism in Germany

Abstract: Anti-immigration sentiments can take on a variety of forms, but a particularly prevalent version across Europe is welfare chauvinism. According to welfare chauvinism, the services of the welfare state should be provided only to natives and not to immigrants. Like many other European countries, German politics also features welfare chauvinism, and not only on the far right segment of the political spectrum. What drives welfare chauvinism? Most studies of welfare chauvinism try to assess whether economic or cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Attitudes towards welfare benefits and different forms of anti-immigrant attitudes, however, seem to be important for predicting welfare chauvinism in all three countries. Despite the link between neoliberalism and welfare chauvinism having often been commented on (Keskinen et al, 2016;Kymlicka, 2020), the empirical link that is found in this study is quite a novel finding, as, to the best of our knowledge, the only other study to empirically confirm that attitudes towards welfare benefits influence welfare chauvinistic attitudes is Grdešić's (2019) study of neoliberal attitudes on welfare chauvinism in Germany.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Attitudes towards welfare benefits and different forms of anti-immigrant attitudes, however, seem to be important for predicting welfare chauvinism in all three countries. Despite the link between neoliberalism and welfare chauvinism having often been commented on (Keskinen et al, 2016;Kymlicka, 2020), the empirical link that is found in this study is quite a novel finding, as, to the best of our knowledge, the only other study to empirically confirm that attitudes towards welfare benefits influence welfare chauvinistic attitudes is Grdešić's (2019) study of neoliberal attitudes on welfare chauvinism in Germany.…”
Section: Discussionmentioning
confidence: 55%
“…We also assume that individual attitudes towards benefits in general may affect welfare chauvinistic attitudes. We build on the notion that neoliberalism and welfare chauvinism share a similarity, as their core idea is to constrain solidarity and to separate the ‘deserving’ from the ‘undeserving’ (Grdešić, 2019). Here, we follow the explanation that neoliberalism is linked to a general position that market forces are beneficial, and that it glorifies individualism, competition and private initiative (Grdešić, 2019).…”
Section: Theoretical Framework: Explanations For Welfare Chauvinismmentioning
confidence: 99%
See 1 more Smart Citation
“…Such radical right-wing parties' messages promoted citizens to internalize the association between neoliberal ideology and anti-immigrant sentiment. This theoretical explanation has been widely accepted in the literature (e.g., Mudde, 1999) and has been used as an underlying assumption in the models of empirical analyses (e.g., Grdešić, 2019;Schmidt & Spies, 2014;Zhirkov, 2014).…”
Section: Contexts Of Moderating the Neoliberal Ideology And Anti-immi...mentioning
confidence: 97%
“…Attitudes towards redistribution have also been found to influence welfare chauvinistic attitudes (Grdešić, 2019; Bell et al, 2022). We therefore create a scale for measuring attitudes towards welfare benefits using four questions where the respondents were asked if they disagree strongly (=1) or agree strongly (=5) with the following statements concerning social benefits/services: (1) Social benefits/services cost businesses too much in taxes/charges; (2) Social benefits/services make people lazy; (3) Social benefits/services make people less willing to care for one another; (4) Social benefits/services place too great a strain on the economy.…”
Section: Introductionmentioning
confidence: 99%